2018
DOI: 10.1080/02656736.2018.1479778
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound-guided transvaginal radiofrequency ablation of uterine fibroids assisted by virtual needle tracking system: a preliminary study

Abstract: Purpose: The purpose of this study was to assess the feasibility and outcome of transvaginal ultrasound (US)-guided radiofrequency ablation of uterine fibroids assisted by a real-time virtual needle tracking (VT) system. Methods: Between January 2017 and February 2018, 19 patients (age 45 ± 8 y, range 36-53 y) with 25 symptomatic uterine fibroids underwent transvaginal radiofrequency ablation (RFA) at a single center. Mean number of fibroids for patient was 1.7 (min, max: 1-3). Patients with more than one fibr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 44 publications
(51 reference statements)
0
14
0
Order By: Relevance
“…Lim et al 5 reported that laparoscopic Bongers et al 15 39 -23 -4.4 -3.1 -Brölmann et al 16 Garza-Leal 17 ----Braun et al 18 114 -60 6.8 -3.2 --Brucker et al 19 66 -24 10.0 -5.5 20.5 (5, 103) a 10.0 (2, 86) a Hahn et al 20 Krämer et al 21 Carrafiello et al 22 20 (15, 25) b ---Cho et al 23 -(10, 40) ---Cho et al 24 ----Chudnoff et al 25 126 -60 -9.0 (2, 60) a 5.0 (0, 29) a Galen et al 26 Guido et al 27 Berman et al 28 Chudnoff et al 29 47 -30 2. 30 Galen et al 31 140 (42, 290) a -4.5 (1, 11) b 4.0 (2, 10) a Garza-Leal et al 32 Robles et al 33 Ghezzi et al 34 25 (20, 45) a 18 c --Bergamini et al 35 Iversen and Dueholm 36 ----Iversen et al 37 Jiang et al 38 25 (20, 30) b ---Kim et al 39 18 -5 ---Lee et al 40 ----Marcos et al 41 36 -11 12.0 (8, 24) b --Meng et al 42 ----Rattray et al 43 73 -26 6.7 -3.0 -11.1 -7.6 Rey et al 44 17 (11, 44) b ---Turtulici et al 45 28 (16, 43) b ---Wu et al 46 -(20, 40) 2.5 c --…”
Section: Discussionmentioning
confidence: 99%
“…Lim et al 5 reported that laparoscopic Bongers et al 15 39 -23 -4.4 -3.1 -Brölmann et al 16 Garza-Leal 17 ----Braun et al 18 114 -60 6.8 -3.2 --Brucker et al 19 66 -24 10.0 -5.5 20.5 (5, 103) a 10.0 (2, 86) a Hahn et al 20 Krämer et al 21 Carrafiello et al 22 20 (15, 25) b ---Cho et al 23 -(10, 40) ---Cho et al 24 ----Chudnoff et al 25 126 -60 -9.0 (2, 60) a 5.0 (0, 29) a Galen et al 26 Guido et al 27 Berman et al 28 Chudnoff et al 29 47 -30 2. 30 Galen et al 31 140 (42, 290) a -4.5 (1, 11) b 4.0 (2, 10) a Garza-Leal et al 32 Robles et al 33 Ghezzi et al 34 25 (20, 45) a 18 c --Bergamini et al 35 Iversen and Dueholm 36 ----Iversen et al 37 Jiang et al 38 25 (20, 30) b ---Kim et al 39 18 -5 ---Lee et al 40 ----Marcos et al 41 36 -11 12.0 (8, 24) b --Meng et al 42 ----Rattray et al 43 73 -26 6.7 -3.0 -11.1 -7.6 Rey et al 44 17 (11, 44) b ---Turtulici et al 45 28 (16, 43) b ---Wu et al 46 -(20, 40) 2.5 c --…”
Section: Discussionmentioning
confidence: 99%
“…More specifically, this system is able to guarantee an in-plane approach by displaying a green line on the B-mode when the axis of the electrode fully matches the US scan plane with the projection of the active tip marked as a square, which becomes smaller as the RF electrode approaches the image plane. From that moment onwards, the path of the RF electrode is represented by a dashed line, the prospective RF electrode path is represented by a dotted line and its active tip is located with a green V [21] (Figure 2). Once the safest path to the target fibroid was identified both via ultrasound (TV or TA) and optically (L-RFMs and H-RFMs), the electrode was appropriately placed into the target fibroid under US real-time guidance and VT [21].…”
Section: Therapymentioning
confidence: 99%
“…From that moment onwards, the path of the RF electrode is represented by a dashed line, the prospective RF electrode path is represented by a dotted line and its active tip is located with a green V [21] (Figure 2). Once the safest path to the target fibroid was identified both via ultrasound (TV or TA) and optically (L-RFMs and H-RFMs), the electrode was appropriately placed into the target fibroid under US real-time guidance and VT [21]. Ablation was performed with the ''moving shot and stepping Once the safest path to the target fibroid was identified both via ultrasound (TV or TA) and optically (L-RFMs and H-RFMs), the electrode was appropriately placed into the target fibroid under US real-time guidance and VT [21].…”
Section: Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…Ultrasound-guided percutaneous MWA is an easy and fast procedure [10] that in recent years has been used to treat uterine fibroids and adenomyosis. Reports are that, for uterine fibroids, the percent volume of the non-enhanced field in the lesion after ablation relative to the volume before ablation (i.e., the ablation rate) ranges from 64.9 to 100% [11,12]. However, all these investigations focused on the changes in the fibroid volume, whereas the ablation effect on blood supply of the fibroid was not addressed.…”
Section: Introductionmentioning
confidence: 99%